IL‐1 receptor antagonist plus pentoxifylline and zinc for severe alcohol‐associated hepatitis. Issue 4 (2nd June 2022) - Szabo, Gyongyi; Mitchell, Mack; McClain, Craig J.; Dasarathy, Srinivasan; Barton, Bruce; McCullough, Arthur J.; Nagy, Laura E.; Kroll‐Desrosiers, Aimee; Tornai, David; Min, Hyesung Alice; Radaeva, Svetlana; Holbein, M. E. Blair; et al.
Abstract: Background and Aims: Patients with severe alcohol‐associated hepatitis (AH) have high mortality. Corticosteroids improve survival only for 30 days. We targeted inflammation, cellular injury, and gut leakiness in a randomized clinical trial comparing combination therapy to corticosteroids on 180‐day survival. Approach and Results: Subjects with a clinical diagnosis of severe AH (Model for End‐Stage Liver Disease [MELD] >20, Maddrey discriminant function [MDF] >32) were randomized to receive methylprednisolone (PRED; 28 days) or a combination of anakinra (14 days) plus pentoxifylline (28 days) plus zinc (COMB; 180 days). The primary endpoint was survival at 180 days. The study was designed in 2013, initiated in October 2014, and completed in March 2018. Five hundred patients were screened to randomize 104 subjects with a clinical diagnosis of AH with a MELD score >20. Fifty‐three patients were randomized into the COMB and 50 to the PRED treatment; 1 dropped out of the study before randomization. Mean age was 45.3 ± 10.4 years; 60.6% were males, 92.3% White, and mean MELD 25.7 ± 3.9. Kaplan‐Meier survival estimate at 180 days was 67.9% in COMB and 56% in PRED (HR = 0.69; p  = 0.3001). Survival curves separated by 90 days (COMB, 69.8%; PRED, 58.0%; HR = 0.69; p  = 0.28). Survival at 28 days was similar between the COMB (83.4%) and PRED groups (81.2%; HR = 0.91; p  = 0.85). There were no unexpected serious adverse events, and incidence of infection was comparable between groups. MELD 20–25 and MELD >26 strata showed nonsignificant treatment effects in favor of COMB. Conclusions: A combination of anakinra, pentoxifylline plus zinc provides similar survival benefits compared to corticosteroid therapy in severe AH. Abstract : In a multicenter randomized clinical trial we targeted the key elements of alcoholic hepatitis including inflammation, cellular injury and gut leakiness and compared combination therapy to corticosteroids on 180‐day survival. Subjects with a clinical diagnosis of severe alcohol‐associated hepatitis AH (MELD>20, MDF>32) were randomized to receive methylprednisolone (PRED) or a combination of the IL‐1 receptor antagonist, anakinra plus zinc plus pentoxifylline. Survival at 28 days was similar between the COMB (83.4%) and PRED groups (81.2%) (HR=0.91, p=0.85). Survival curves separated by 90 days (COMB: 69.8%; PRED: 58.0%; HR=0.69, p=0.28). Survival at 28 days was similar between the COMB (83.4%) and PRED groups (81.2%) (HR=0.91, p=0.85). There were no unexpected serious adverse events. These results suggest that a combination of anakinra, pentoxifylline plus zinc provides similar survival benefits compared to corticosteroid therapy in severe AH.